Delineation of multiple metamorphic events in the Himalayan Kathmandu Complex, central Nepal. (15th December 2020) - Johnson, Thomas A.; Cottle, John M.; Larson, Kyle P.
Abstract: Quartz‐inclusion geothermobarometry of texturally and chemically zoned garnet, together with U–(Th)–Pb accessory phase petrochronology, phase equilibria modelling, and major element thermobarometry delineates two metamorphic events within the Kathmandu Complex in central Nepal. Combined titanium‐in‐quartz thermometry (TitaniQ) and quartz‐in‐garnet barometry (QuiG) of quartz inclusions in garnet cores yields temperatures and pressures (555–580°C, 0.89–0.91 GPa) statistically higher than those estimated for both garnet rims and secondary garnet neoblasts (535–545°C, 0.81–0.84 GPa). Comparison of these temperatures and pressures with the results from phase equilibria modelling indicates that the garnet cores nucleated after overstepping the equilibrium garnet isograd. Estimation of the degree to which overstepping may have occurred, however, is complicated by uncertainty in the estimated reactive bulk compositions. Major element thermobarometry of the garnet rims returns temperatures and pressures lower than those preserved by the garnet cores but are consistent with previous estimates of Cenozoic metamorphism in the frontal portion of Kathmandu thrust sheet. Two generations of titanite are recognized on the basis of mineral morphology, chemical zoning, and U–Pb date ( c . 500 Ma versus 29 ± 5 Ma). Trace‐element systematics of the two titanite populations indicate varying co‐stability with allanite and are consistent with Th–Pb dates of allanite growth ( c . 489 Ma) and breakdown to clinozoisite ( c . 30 Ma). Inclusion patterns within titanite indicate that the younger group formed following breakdown of rutile that originally coexisted with the older generation of titanite at pressures and temperatures similar to those determined from the garnet cores. Application of the Zr‐in‐titanite and Zr‐in‐rutile thermometers yields temperatures 100–150°C in excess of those indicated by both TitaniQ‐QuiG and major element thermobarometry. This discrepancy is interpreted to reflect disequilibrium partitioning of Zr and limited zircon reactivity during metamorphism. Collectively, these observations are consistent with previous estimates of the timing and conditions of metamorphism associated with the Palaeozoic Bhimphedian and Cenozoic Himalayan orogenies in central Nepal. The estimated temperatures and pressures for growth of the garnet cores are consistent with rapid burial during thrust stacking.